The Great Equal Society : Confucianism, China and the 21st Century. - Kim, Young-oak (World Scientific Publishing Company, 2013)
Confucianism is the guiding creed for a quarter of mankind, yet hardly anyone has explained it in plain terms - until now. Written in a style both intelligible and enjoyable for the global audience, The Great Equal Society distils the core ideas of the major Confucian classics and shows how their timeless wisdom can be applied to the modern world. It also introduces pragmatic suggestions emanating from Confucius and his followers for ensuring good governance, building a humane economy and educating moral leaders. The book's core message of inner morality, first expounded by Confucius millennia.